A High‐Performance Na–Al Battery Based on Reversible NaAlCl4 Catholyte. Issue 40 (2nd September 2020) - Zhan, Xiaowen; Bonnett, Jeffrey F.; Engelhard, Mark H.; Reed, David M.; Sprenkle, Vincent L.; Li, Guosheng
Abstract: This work demonstrates a high‐capacity and safe Na–Al battery pairing a sodium metal anode and reversible NaAlCl4 catholyte for grid scale energy storage applications. The energy‐rich Na anode allows the full use of the aluminum cathode, resulting in a full‐cell capacity of 308 mAh g −1 at a discharge voltage of 1.6 V. Benefiting from the use of a β″‐alumina solid electrolyte, molten sodium anode, and reversible Al deposition/stripping from NaAlCl4 catholyte, the battery presents a stable Coulombic efficiency of 100% and energy efficiency of ≈95%. At a rate of C/3 (6.77 mA cm −2 ), the cell maintains 282 mAh g −1 (447 Wh kg −1 ) after 200 cycles with an excellent capacity retention of 97.6%. Moreover, pathways to build Na‐anode‐free cells from the discharged state under dry air are elucidated, which further extends the feasibility of this battery for stationary storage applications. These findings are expected to provide a new platform for the development of practical aluminum batteries. Abstract : An advanced, low cost (due to the use of earth‐abundant Al and NaCl), high energy (≈450 Wh kg −1 ) Na–Al battery with excellent long‐term cycling stability is presented. Pathways are elucidated to build sodium‐anode‐free cells from the discharged state under dry air, which further extends the feasibility of this battery for stationary storage applications.